Pengembangan Sistem Manajemen Sampah TPS3R Dinas Lingkungan Hidup Kota Batu berbasis Web Responsive menggunakan Tailwind dan ReactJS - Ignatius Daniel Y.T.A. Ginting; Herman Tolle; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Reduce, Reuse, Recycle Waste Management Site (TPS3R) is a system that functions to manage waste from households and industries to reduce environmental pollution. In TPS3R waste management, it is necessary to collect data on the amount of incoming and processed waste in order to determine the efficiency of waste management at TPS3R sites. In this case, the Batu City Environmental Service obtained the data through calculations carried out by TPS officers who were on the TPS3R site around Batu City villages and sub-districts. However, the process of recording waste data is still done manually so that the analysis of the efficiency of waste management in TPS3R is still not optimal. To overcome this problem, a web-based waste management application was developed with adding and viewing waste data features to facilitate data processing carried out by the Environmental Service at TPS3R in Batu City. This study uses the waterfall method to develop the TPS3R waste management system. Based on the tests that have been carried out, namely validation testing which produces a value of 100% for each test case and Compability testing is carried out using the sortsite test tool which results in the system running well on the 7 browser versions that have been tested. Meanwhile, the usability test conducted on 5 respondents using the System Usability Scale (SUS) yielded a value of 78, thus proving that the usability of the system can be said to be good.